DAMPAK PEMBERITAAN COVID19 DI MEDIA SOSIAL TERHADAP PERILAKU MASYARAKAT DI DUSUN KEMUNING KELURAHAN LIRBOYO KOTA KEDIRI - Fifi Listia Sari (Jurnal Mediakita : Jurnal Komunikasi dan Penyiaran Islam, 2020)
Covid19 has been declared a pandemic by WHO (World Healthy Organization). Its rapid spread makes the government give orders for Work From Home and Study From Home. The number of activities carried out at home makes many people use social media with increasing duration. Covid19 coverage circulated was offered more than any other news. This makes the user experience a change of mindset to action and makes the writer interested in examining the impact of covid19 reporting on social media on community behavior in the Kemuning hamlet of Lirboyo, Kediri. To analyze these problems the writer uses a qualitative suppressor with descriptive analysis and uses social media theory as well as behavior theory. The purpose of this research is to describe the impact of covid19 reporting on social media on community behavior in the Kemuning sub-village of Lirboyo, Kediri. The main source of data from the results of interviews and also books and journals. Repeated news about covid19 and the enormous impact on change ranging from social and economic to make people aware that this virus is very dangerous. In addition, the community feels anxiety because of the increasing number of patients and other factors. Covid19 news is always updated. This behavior change appears in the yellow environment. In this case the community has a good mindset following the government's recommendations, starting from washing their hands after their activities outside the home, seen from many water boxes and hand washing soap in front of the house. Besides that, the people of the town of Kediri also wear masks when they are outside, even though they are not too far away. So in reporting covid19 on social media has positive and negative psychological and behavioral impacts.